1982
DOI: 10.1136/bmj.284.6333.1901
|View full text |Cite
|
Sign up to set email alerts
|

Distributions of birth weight in seven Dublin maternity units.

Abstract: Differences in birthweight distribution among babies born to Dublin residents during one year in seven maternity units were analysed. Large differences were found between the hospitals. The evidence indicated that most of the difference was attributable to the differing socioeconomic profile of the mothers in the hospitals. The socioeconomic gradients shown by the hospitals in the proportions of babies weighing < 2500 g, < 3000 g, and 3001-4499 g diverged with increasing socioeconomic disadvantage. Steepest gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…± 2 weeks, contrasted with Caucasian births which peaked 31% at 41 weeks gestation, mean gestation of 41.03 weeks S.D. ± 1.32 weeks, with a highly statistically significant difference of 3-4 weeks (p=0.001), while Norway reported mean gestation of 40 weeks 3 days [101,104,105,108]. The shortened gestation of 38 weeks at peak births among Asian-Indian babies results in smaller babies with lower average birth weight 2881g when compared to Caucasian newborns who with a longer gestation upto 42-44 weeks continue to gain weight by deposition of subcutaneous fat have birth weight around 3500g [101,105,106,108,110].…”
Section: Lnr Includes 3 Stepsmentioning
confidence: 99%
See 4 more Smart Citations
“…± 2 weeks, contrasted with Caucasian births which peaked 31% at 41 weeks gestation, mean gestation of 41.03 weeks S.D. ± 1.32 weeks, with a highly statistically significant difference of 3-4 weeks (p=0.001), while Norway reported mean gestation of 40 weeks 3 days [101,104,105,108]. The shortened gestation of 38 weeks at peak births among Asian-Indian babies results in smaller babies with lower average birth weight 2881g when compared to Caucasian newborns who with a longer gestation upto 42-44 weeks continue to gain weight by deposition of subcutaneous fat have birth weight around 3500g [101,105,106,108,110].…”
Section: Lnr Includes 3 Stepsmentioning
confidence: 99%
“…Congo, Egypt and Thailand with 400g less birth weight median, while Argentina, Brazil and France had birth weight less than 200g and Denmark, Germany with mean birth weights approximately 100 g less. WHO has also observed that differences in birth weight when adjusted to gestational age at birth between other countries is highly significant for all percentiles at birth, p=0.0018 at 5 th percentile to p<0.001 for 10 th , 25 th , 50 th , 75 th , 90 th and 95 th percentiles, reveals the wide variation in human fetal growth across ethnic Asian and Caucasian population, indicating that Asian and Caucasian perinatal definitions are mandated, taking into consideration the wide variation in mean birth weight gestation at birth and intrauterine growth pattern based on ethnicity that will result in improved perinatal and neonatal outcome among ethnic Asian population, presently comprising a majority four-fifths of world's nearly 8 billion population [106][107][108][109]. The Asian Indian peak births 32.6 % in 1983 cohort occurred at 39 weeks gestation with mean gestation of 38.86 weeks S.D.…”
Section: Lnr Includes 3 Stepsmentioning
confidence: 99%
See 3 more Smart Citations